2017
DOI: 10.1073/pnas.1711243115
|View full text |Cite
|
Sign up to set email alerts
|

Brain urea increase is an early Huntington’s disease pathogenic event observed in a prodromal transgenic sheep model and HD cases

Abstract: The neurodegenerative disorder Huntington's disease (HD) is typically characterized by extensive loss of striatal neurons and the midlife onset of debilitating and progressive chorea, dementia, and psychological disturbance. HD is caused by a CAG repeat expansion in the Huntingtin (HTT) gene, translating to an elongated glutamine tract in the huntingtin protein. The pathogenic mechanism resulting in cell dysfunction and death beyond the causative mutation is not well defined. To further delineate the early mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 62 publications
7
75
0
Order By: Relevance
“…For example, it was reported that brains of patients suffering from Huntington's disease (HD) contain about threefold more urea compared to the healthy controls (Patassini et al 2015). These findings have been proved in a transgenic sheep model of HD (Handley et al 2017) Additionally, the data indicating that the postmortem brains of AD patients contain significantly higher concentrations of urea compared to the control group have been published recently (Xu et al 2016). Consequently, the hypothesis linking build-up of urea in the brain to toxic levels causing brain damage and finally dementia was proposed (Handley et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that brains of patients suffering from Huntington's disease (HD) contain about threefold more urea compared to the healthy controls (Patassini et al 2015). These findings have been proved in a transgenic sheep model of HD (Handley et al 2017) Additionally, the data indicating that the postmortem brains of AD patients contain significantly higher concentrations of urea compared to the control group have been published recently (Xu et al 2016). Consequently, the hypothesis linking build-up of urea in the brain to toxic levels causing brain damage and finally dementia was proposed (Handley et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been verified in a transgenic sheep model of HD [77]. Consequently, a hypothesis was proposed that links the build-up of urea in the brain to toxic levels, causing brain damage and, finally, dementia [77].…”
Section: Plantsmentioning
confidence: 85%
“…For example, it has been reported that the brains of patients suffering from Huntington's disease (HD) contain about threefold more urea compared to healthy controls [76]. This finding has been verified in a transgenic sheep model of HD [77]. Consequently, a hypothesis was proposed that links the build-up of urea in the brain to toxic levels, causing brain damage and, finally, dementia [77].…”
Section: Plantsmentioning
confidence: 99%
“…The enrichment analysis also revealed defective ammonia recycling in SCA7. Since ammonia easily crosses the blood-brain barrier, blood-derived ammonia leads to neurotoxic levels of ammonia in the brain [44]. Aside from primarily affecting the brain, the toxicity of ammonia has also been demonstrated to affect other organs and tissues, including muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, muscle mass depletion further reduces the body's capacity to clear ammonia, which in turn leads to a higher risk of developing hyperammonemia. Interestingly, both HD and SCA7 patients have elevated plasma ammonia levels [44], therefore it is tempting to speculate that dysregulated brain energy metabolism in SCA7 patients could be facilitated, at least in part, through imbalances in ammonia homeostasis.…”
Section: Discussionmentioning
confidence: 99%